DETERMINANTS OF YOUNG PEOPLE'S INTEREST IN BECOMING RICE FARMERS IN PENEBEL DISTRICT, TABANAN REGENCY, BALI PROVINCE - I Nyoman Mertadana; Ni Made Tisnawati (Adisam Publisher, 2026)
The sustainability of the agricultural sector in Penebel District is currently facing serious challenges due to the declining interest of the younger generation in pursuing rice farming as a profession. This study was designed to examine: (1) the contribution of motivation, perceptions of agriculture, agricultural experience, gender, educational level, parents’ occupation, availability of family-owned rice fields, and family economic conditions to young people's interest in becoming rice farmers; (2) the moderating role of perceptions of agriculture on the relationship between family economic conditions and such interest; and (3) the most dominant factor influencing this interest. The study involved 100 young farmers aged 19–39 years who were selected through accidental sampling in Penebel District, Tabanan Regency. Data collected through observation, questionnaires, and interviews were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach with SmartPLS 3 software. The findings indicate that motivation, agricultural experience, parents’ occupation, availability of family-owned rice fields, family economic conditions, and perceptions of agriculture have a positive and significant effect on increasing young people's interest in rice farming. Among these variables, motivation was identified as the most influential factor. Furthermore, perceptions of agriculture negatively moderate (weaken) the effect of family economic conditions on such interest. In contrast, gender and educational level were found to have no significant effect. These findings imply the importance of government initiatives in promoting technology-based modern agriculture and protecting the availability of rice fields through agricultural land zoning regulations.